SUPERVISI PEMBELAJARAN DALAM MENINGKATKAN SEMANGAT MENGAJAR GURU - Hidayanti, Laras; Maunah, Binti; Mutohar, Prim Masrokan (Educational Leadership: Jurnal Manajemen Pendidikan, 2024)
This journal discusses with the learning supervision in boostingthe spirit of teaching teachers. As for the focus on this journal is 1) the concept of learning supervision 2) the concept of teaching teacher 3) the implementation of supervision learning in raising the teacher's spirit. The purpose of this scientific journal is to describe the learning supervision in raising the teacher's spirit. it uses literature analysis methods that make use of library resources to obtain theories and restrict activities to library items and other factual references.